Magnesium Biomaterials Design, Testing, and Best Practice - Kirkland, Nicholas Travis; Birbilis, Nick (SpringerBriefs in Materials, 2014)
Magnesium Biomaterials provides a succinct up-to-date overview of Magnesium biomaterial development, critically examines the types of in vitro experiments that may be performed, and investigates the numerous variables that affect Magnesium biodegradation when undertaking these experiments. This work also discusses the direction in which current Magnesium biomaterial development is heading and the necessary steps for future development of this field. Information is drawn from numerous multi-disciplinary sources to provide a coherent and critical overview. Magnesium Biomaterials is ideal for researchers in the area of bio-Mg, companies interested in exploring their own alloys, and for researchers working with other biodegradable materials who are seeking a cross-platform understanding of material performance.